THE IMPORTANCE OF NATIONAL VALUES IN THE DEVELOPMENT OF PRESCHOOL CHILDREN - Usmanova M. S. (Journals Park Publishing, 2022)
The roots of the culture of the Uzbek people go back to the distant past. Our people have been striving for goodness and doing creative work throughout their lives. Pre-school educational institutions have their own ways of education and training, which are carried out in order to raise children as well-rounded and well-rounded individuals.